On the Periodical Nature of Annual Variation of the Regressions of the Martian Polar Caps Using the Phase Dispersion Minimization-(PDM) Method - Iratius Radiman; Chatief Kunjaya; Andreas Widjaja (Institut Teknologi Bandung, 1998)
Data observations of the regressions of the Martian Polar Caps from 1905 to 1988 were reinvestigated through the Stellingwerfâs Phase Dispersion Minimization-(PDM) method. The results indicate that the annual variations of the regressions of the Martian Polar Caps is seen to have a periodical nature. The main period is found to be approximately 40 years while other periodical components of shorter duration seen in the data also exist. The shorter periods are 3, 6 and 8 years respectively. The 3 years period may be attributed to the systematic effect of 2-3 years interval in which the data was acquired. The 6 years may be a subharmonic component of the 3 years period, though it is blended. The 8 years period cannot be attributed to the same effects of observations, such as the cyclic appearances of each polar caps in the Martian epoch of observations. Irregularity of the epoch interval of observations prevent such a systematic effect to be seen. Therefore, we like to point out that the 8-years period is a real physical phenomenon of the annual variations of the polar regressions. This strongly support the findings of Iwasaki and Ebisawa on sizes of the South Polar Cap. The PDM-method is sufficiently general to analyze small sets of data involving missing observations and non-sinusoidal time variations. The method was used to ascertain results obtained previously through time-series calculations which involved missing observations. Discussions on probable relations between changes in solar radiation which might affect the annual regressions of the polar caps are also examined.